Excel 2016 Power Programming with VBA. - Alexander, Michael, 1972-; Kusleika, Dick (John Wiley & Sons, Inc., 2016)
Encompassing an analysis of Excel application development and a complete introduction to Visual Basic for Applications (VBA) - with over 800 pages of tips, tricks, and best practices, this comprehensive book presents all of the techniques you need to develop both large and small Excel applications. - Resumé vydavatel
Keywords: Microsoft Excel (Computer file); vizuální programovací jazyky; grafické programování; Microsoft Excel 2016 (software); obchod; tabulkové procesory; visual programming languages; graphical programming; commerce; electronic spreadsheets; elektronické knihy; příručky; electronic books; handbooks and manuals